Associations of Leptin and Pituitary‐Specific Transcription Factor Genes' Polymorphisms with Reproduction and Production Traits in Dairy Buffalo. (23rd June 2016) - Nasr, MAF; Awad, A; El Araby, IE
Contents: This study aimed to detect the genetic variability in Leptin and Pit‐1 genes using polymerase chain reaction–restriction fragment length polymorphism and DNA sequencing also to explore their possible associations with reproductive and productive traits of Egyptian buffaloes. Regarding Leptin gene, three genotypes (AA, AG and GG) were identified with frequency of 0.54, 0.40 and 0.06, respectively, and the genotypes were distributed according to the Hardy–Weinberg equilibrium. Allele A was comparatively higher than G with frequency of 0.74 and 0.26, respectively. For Pit‐1 gene, the association could not be performed due to the monomorphism (BB). The results showed that AA genotypes were found to be superior in most of production and reproduction traits. AA genotypes yielded more milk (2332.34 kg, p = 0.04) with higher fat% (6.10, p = 0.004) and fat yield (155.75 kg, p = 0.06), reach peak milk production at 42.19 days and required 2.19 services for conception in comparison with GG genotypes. Birthweight of animals with AA genotype was lesser than with GG genotype (39.35 and 43.67 kg, p = 0.02, respectively). The days open is numerically better in AA genotype animals (99.35 days), but the difference between the three genotypes was non‐significant. The distinct significant associations reported in this study suggested that Leptin is reputable candidate genetic marker, which might be used to enhance animals' genetic potential for milk production in conjunction with reproduction.